KEDUDUKAN ANAK LAKI-LAKI DAN ANAK PEREMPUAN SUKU SASAK LOMBOK DALAM PEMBAGIAN HARTA WARIS (Studi Kasus Di Dusun Adat Sade Kabupaten Lombok Tengah) - Wahyu Aolia; Ketut Sudiatmaka; Dewa Bagus Sanjaya (Universitas Pendidikan Ganesha, 2023)
This research aims to (1) find out how the position of boys and girls in the division of inheritance according to customary law in Sade Hamlet is related to the legal pluralism that exists in the Sasak tribe community. (2) To find out which laws apply in the distribution of inheritance according to customary law in Sade Hamlet. The type of research used is empirical legal research. The legal materials used come from legal, primary, secondary and tertiary materials. Data collection techniques use documentation study techniques, interviews and direct observation. The results and conclusions of the research show that the position of sons and daughters in the division of inheritance in the Sade traditional hamlet still adheres closely to and maintains the customary law that has been in force from the past until now in matters of distribution of inheritance according to the principle of the family system adhered to by children. Men as the successors of the lineage receive absolute inheritance of inheritance. The community in Sade Hamlet adheres to a patrilineal family system. This results in daughters not having the right to inherit property from their parents. The indigenous people in the Sade traditional hamlet are strictly subject to local customary regulations.